“Honor” in Rhodes: Dio Chrysostom’s thirty-first oration - Bailey, Colin (My University, 2015)
This article argues that Dio Chrysostom’s thirty-first Oration offers a commentary on the condition of the Greek polis in a Roman world. Dio addresses the practice of re-using statues in order to show the role that the past plays in contemporary constructions of identity. Statues honoring past benefactors enable present citizens, and therefore Rhodes, to compete with those past benefactors and to live up to their full potential. Dio shows that it is a failure to contend with past benefactors that threatens the ability of the polis to be a polis.